Thiophene bioisosteres of GluN2B selective NMDA receptor antagonists: Synthesis and pharmacological evaluation of [7]annuleno[b]thiophen-6-amines. Issue 2 (15th January 2020) - Baumeister, Sören; Schepmann, Dirk; Wünsch, Bernhard
Graphical abstract: Abstract: Thiophene bioisosteres of potent GluN2B receptor negative allosteric modulators were prepared and evaluated pharmacologically. The five-step synthesis of 4, 5, 7, 8-tetrahydro[7]annuleno[b]thiophen-6-one (10 ) was considerably improved by carboxylation of thiophene-3-carboxylic acid (8 ) in the first reaction step. Reductive amination and alkylation led to three homologous series of secondary and tertiary phenylalkylamines 5, 11 and 12 . Metalation, reaction with 1-formylpiperidine and subsequent reduction provided hydroxymethyl derivatives 15 and 16, which had been designed as bioisosteres of phenols. 2-Bromo derivatives 18 were obtained by bromination of ketone 10 with NBS and subsequent reductive amination. High GluN2B affinity was achieved with [7]annuleno[ b ]thiophenes bearing a 3-phenylpropylamino or 4-phenylbutylamino moiety (e.g. 5c : K i = 5.9 nM; 11d : K i = 9.0 nM). Tertiary ethylamines 12 showed lower GluN2B affinity than tertiary methylamines 11 or secondary amines 5 (e.g. 5c : K i = 5.9 nM; 11c : K i = 6.0; 12c : K i = 51 nM). A Br-atom or a hydroxymethyl moiety in 2-position were less tolerated by the GluN2B receptor. Very similar relationships between the structure and GluN2B affinity and structure and σ affinity, in particular σ2 affinity, were detected. A slight preference for the ifenprodil binding site of GluN2B receptors over σ1 and σ2 receptors was found for methylamines 11c (≈2-fold) and 11d (≈1.5–2-fold) as well as for bromo derivative 18c (≈3-fold).